Pelatihan Pengucapan (Pronunciation) Kata-Kata Asing Populer untuk Meningkatkan Kemampuan Bahasa Inggris Gen Z di Pesantren di Jawa Tengah - Harsiwi, Windy; Fatimah, Rezky; Muthmainnah, Yuni Mardiyah; Winanto, Alfa Rizqi (Jurusan Teknik Informatika dan Komputer, 2025)
This pronunciation training program for popular foreign words was conducted to enhance the English language skills of Generation Z (Gen Z) students in Islamic boarding schools (pesantren) in Central Java. In this era of globalization and digital media dominance, the ability to communicate effectively—especially through accurate pronunciation—has become a crucial asset for global competitiveness. However, many students still struggle with English pronunciation due to limited teaching methods, a lack of English-speaking environments, and minimal use of educational technology. This training program was designed using an interactive, technology-based approach, including mobile applications (such as Elsa Speak and HelloTalk), online conversations with native speakers, and intensive training supported by audio-visual media. These methods allowed students to identify and correct common pronunciation errors independently and sustainably. The results indicated significant improvements in pronunciation accuracy, communication confidence, and student enthusiasm for learning. Furthermore, the program strengthened the capacity of pesantren as adaptive educational institutions aligned with modern challenges and global demands. Through this training, students gained not only technical skills in pronunciation but also new insights into the importance of cross-cultural communication and the role of technology in language learning. This program represents a tangible contribution from Diponegoro University to community empowerment and education quality improvement through the dissemination of multidisciplinary research and community service outcomes. The evaluation results indicate an increase in students' pronunciation scores based on ELSA Speak application analysis, with most participants reporting improved confidence in communication. The training also encouraged the adoption of self-directed learning technology, with the majority of students actively using pronunciation practice applications on an ongoing basis.